Propuesta metodológica para la estimación y análisis del impacto de escenarios de cambio climático en la calidad del agua de ríos tropicales de montaña. Caso de estudio: Río Bogotá - Colombia (2022)
Climate change is causing changes in the variables and hydrological cycle processes at the watershed level, with the potential to impact water quality in rivers. This research proposes a methodology to quantify and analyze how climate change affects water quality in tropical mountain rivers. The proposed methodology is applied to the upper Bogota river basin in the Andes of Colombia. Using the global climate models available in the Coupled Model Intercomparison Project (CMIP5) database, the ensemble method was applied to determine climate change scenarios for mean precipitation and mean temperature in the river basin, using the radiative forcing scenarios RCP 2.6, RCP 4.5, RCP 6.0, and RCP 8.5. Then, by modeling the river basin in QUAL-2k, the current river water quality scenario is compared with the four radiative forcing scenarios under wet, dry, and average hydrological conditions. The achieved results show that the progressive increase in CO2 partial pressure will generate a decrease in water pH, which will impact the processes associated with water supply and treatment. On the other hand, the results show that the progressive increase in temperature contributes to an acceleration of the reaction rates of the bio-chemical processes of hydrolysis, oxidation, nitrification and death of organic pollutants, nutrients, and the death of pathogenic organisms, respectively. The increase in these reaction rates will lead to a decrease in dissolved oxygen during the oxidation of organic matter and nitrification. As an opposite effect, the progressive increase in the flow rate predicted under the effects of climate change will increase the dilution and assimilation of organic pollution in the upper Bogotá river basin.